2024
DOI: 10.3390/s24041089
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cognitive Workload in Motor Decision-Making through Functional Connectivity Analysis: Towards Early Detection and Monitoring of Neurodegenerative Diseases

Leonardo Ariel Cano,
Ana Lía Albarracín,
Alvaro Gabriel Pizá
et al.

Abstract: Neurodegenerative diseases (NDs), such as Alzheimer’s, Parkinson’s, amyotrophic lateral sclerosis, and frontotemporal dementia, among others, are increasingly prevalent in the global population. The clinical diagnosis of these NDs is based on the detection and characterization of motor and non-motor symptoms. However, when these diagnoses are made, the subjects are often in advanced stages where neuromuscular alterations are frequently irreversible. In this context, we propose a methodology to evaluate the cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…For instance, prior studies in right-handed participants [ 45 , 46 ] showed broad activation across parietal and frontal regions in the left hemisphere during movements for either hand, whereas activation of homologous regions only in the right hemisphere tends to be more limited to left-hand actions. This evidence suggests that the motor planning in control participants differs between hemispheres, as observed in our previous work [ 25 ]. This could be explained by the greater inhibitory mechanisms of the left hemisphere for the right hand during movement preparation in right-handers, as suggested by Klein et al [ 37 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For instance, prior studies in right-handed participants [ 45 , 46 ] showed broad activation across parietal and frontal regions in the left hemisphere during movements for either hand, whereas activation of homologous regions only in the right hemisphere tends to be more limited to left-hand actions. This evidence suggests that the motor planning in control participants differs between hemispheres, as observed in our previous work [ 25 ]. This could be explained by the greater inhibitory mechanisms of the left hemisphere for the right hand during movement preparation in right-handers, as suggested by Klein et al [ 37 ].…”
Section: Discussionsupporting
confidence: 83%
“…This synchronization ensured continuous alignment of all three types of signals, thereby preventing any lag or delay that could compromise data accuracy. Extensive details of the instrumental setup can be found in a previous study [ 25 ]. The three types of signal are depicted in Figure 2 A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation